Landscape Characterization and Modeling Degradation by Fragmentation of Plant Formations: Case of Ketu and Dogo Classified Forest (East Center of Benin) - TCHIBOZO, ERIC ALAIN MAHUGNON (My University, 2014)
This paper aims to characterize the landscape of classified forests of Kétou and Dogo and model degradation by fragmentation of its plant formations. A multi-criteria methodology for the extraction and use of geographic information has been used to treat Lands a timages and determine the effect size fragmentation mesh. The results show that the spatial structure of the two forest studyis disrupted by the landscape dynamics evaluated over the 2000to 2013 period. The set of natural vegetation under the crops and fallow land pressure has become more important in the Ketu forest with an increase of26.83% and less important in that of Dogo with a24.67%decline.The first forest is characterized by a diversification of the landscape, while the second that of Dogo shows a simplification. Plant formations are fragmented at various levels. Patches very small areas(0.0056 hectares -44.80hectares)are relatively more important for forests and savannas of Dogo than for Ketu. In this lastforest,52.96% of all vegetation is fragmented with patches of less than25 hectares, while in the Dogo, this criticism fragmentation represents a proportion of24.95%. This situation shows that forest structure and bio diversity are already targeted deep and lasting affected. Fragmentation maps are performed on each forest study. Two groups of vegetation degradation factors were identified: physical (the fractures and lineaments network, weathered rocks, bare soil and surface water) and anthropogenic factor (the mosaic of crop and fallow). A linear function of the degradation of vegetation from these factors has been proposed for each forest study, as well as two scenarios for their simulation.
Keywords: Fragmentation; classified forests; vegetation; east - Center of Benin.